Hubungan Anemia Kehamilan, Status Ekonomi dan Pola Pemberian Makan dengan Kejadian Stunting pada Anak di Puskesmas Pemenang, Kabupaten Lombok Utara - Nayna Aulia Lubis; Lalu Irawan Surasmaji; I Gede Angga Adnyana; Hilda Santosa (Universitas Malahayati Lampung, 2025)
ABSTRACT Stunting refer to impaired physical and cognitive growth. It is often caused by prolonged malnutrition. This Condition is influenced by several factors, such as history of pregnancy-related anemia, feeding patterns, and economic status. Understanding the relationship between these factors is Important for stunting control and prevention. This study investigates the correlation between history of pregnancy-related anemia, feeding patterns, and economic status with the incidence of stunting at Puskesmas Pemenang in North Lombok Regency. This study was an analytical observational with cross-sectional design approach. A total of 91 participants were selected through non-probability purposive sampling. The Study was conducted at Puskesmas Pemenang, North Lombok Regency, in September 2024. The data obtained were analyzed through the Chi-square test, with a significance threshold established at p0.05. Univariate analysis revealed that 41 (45.1%) children exhibited stunting, 49 (53.8%) mothers had a history of pregnancy-related anemia, 35 (38.5%) respondents demonstrated inappropriate dietary patterns, and 68 (74.7%) respondents were classified as having an economic status below the minimum wage. Bivariate analysis revealed a statistically meaningful correlation between a history of pregnancy-related anemia and stunting, yielding a p-value of 0.002 (PR: 2.33; 95% CI: 1.343-4.070). Additionally, a significant association was found between inappropriate dietary patterns and the incidence of stunting, with a p-value of 0.001 (PR: 3.08; 95% CI: 1.894-5.028). Conversely, no significant association was observed between economic status and the incidence of stunting, with a p-value of 0.165 (PR: 1.64; 95% CI: 0.847-3.185). History of pregnancy-related anemia and inappropriate dietary patterns are strongly linked to the occurrence of stunting in a statistically significant manner. In contrast, economic status does not show a significant statistical association with the incidence of stunting. Keywords: Stunting, Child Nutrition, Maternal and Child Health, Dietary Patterns, Pregnancy-Related Anemia, Economic Status. ABSTRAK Stunting merupakan suatu kegagalan pertumbuhan pada tubuh dan otak anak. Hal ini muncul sebagai akibat dari kekurangan gizi dalam waktu yang lama. Stunting dipengaruhi oleh beberapa faktor seperti riwayat anemia kehamilan, pola pemberian makan dan status ekonomi. Mengetahui hubungan berbagai faktor ini penting untuk pencegahan dan pengendalian stunting. Mengetahui hubungan antara riwayat anemia kehamilan, pola pemberian makan dan status ekonomi dengan kejadian stunting pada Puskesmas Pemenang, Kabupaten Lombok Utara. Penelitian ini adalah penelitian kuantitatif-observasional, dengan desain cross-sectional. Penelitian ini menggunakan 91 sampel dengan metode purposive sampling. Penelitian dilakukan di Puskesmas Pemenang, Kabupaten Lombok Utara pada bulan September 2024. Data yang diperoleh dianalisis dengan uji Chi-square dengan nilai signifikansi p0,05. Hasil analisis univariat menunjukkan 41 (45,1%) anak mengalami stunting, 49 (53,8%) ibu memiliki riwayat anemia kehamilan, 35 (38,5%) responden memiliki pola makan tidak tepat dan 68 (74,7%) responden memiliki status ekonomi dibawah UMR. Analisis bivariat pada riwayat anemia kehamilan dan stunting menunjukan hubungan yang signifikan dengan nilai p: 0,002 (PR: 2,33; CI 95%: 1,343-4,070). Hubungan signifikan juga didapatkan antara pola pemberian makan dan stunting dengan nilai p 0,001 (PR: 3,08; CI 95%: 1,894-5,028). Antara status ekonomi dan kejadian stunting tidak menunjukan hubungan yang signifikan, dengan nilai p: 0,165 (PR 1,64; CI 95%: 0,847-3,185). Riwayat anemia pada masa kehamilan dan pola pemberian makan berhubungan signifikan secara statistik dengan kasus stunting. Antara status ekonomi dan kejadian stunting juga tidak menunjukan hubungan yang signifikan. Kata Kunci: Stunting, Gizi Balita, Kesehatan Ibu dan Anak, Pola Makan Balita, Anemia Kehamilan, Status Ekonomi Keluarga